Identification Of Resistance Source Against Wilt Disease Of Cumin Caused By Fusarium Oxysporum F.S.P Cumini (Journal of Plant Disease Sciences, 2022)
During Rabi 2020-21, an experiment was carried out at GTC Farm, College of Agriculture, Jodhpur to evaluate cumin genotypes under natural epiphytotic conditions for their resistance to wilt disease (Fusarium oxysporum f.sp. cumini). Under natural epiphytotic conditions, 30 cumin genotypes were screened. There was no resistance or high resistance to wilt disease found in any of the germplasm tested. Four germplasm, GC-4, MCU-34, MCU-51 and MCU-58, showed 11-20 % disease incidence and were classified as moderately resistant. Seventeen germplasm samples were found to have a disease incidence of 21-30 %and were classified as moderately susceptible. Six germplasm were found to have 31-50 per cent disease incidence and were classified as susceptible, while three germplasm, MCU-80, MCU-78 and MCU-59, were found to have > 50 per cent disease incidence and were classified as highly susceptible in the current study.
Keywords: Cumin; Fusarium; oxysporum f.sp. cumini; Genotype; Screening